IMPACT OF THE THREE GORGES WATER CONSERVANCY PROJECT ON RADIOACTIVITY CONCENTRATION LEVELS IN SURROUNDING WATERS. Issue 4 (30th May 2020) - Yang, Qiang; Shao, Yang; Du, Hengyan; Lin, Xuefeng; Wang, Lei; Luo, Ziyi; Ge, Liangquan; Wang, Erqi
Abstract: Large-scale water conservancy projects bear much economic and social significance. However, there is a lack of systematic research on how such projects affect radioactivity levels in regional water bodies. For the first time, the present paper uses data for nearly 10 y at different impoundment levels during construction of the dam to analyze changes in water radioactivity concentration levels in China's Three Gorges region, in order to provide a valuable reference for evaluating the impact of large-scale water conservancy projects on radioactivity concentration levels. Results show that gross α, gross β, U, Th, 226 Ra, 40 K, 90 Sr and 137 Cs levels in the water bodies of the Three Gorges region fall within normal limits and annual effective dose for the adults, children and infants are below the WHO recommended reference level of 0.1 mSv per y. The period where the sample was collected and spatial distribution are the main reasons why some radionuclides are not normally distributed. Different water levels during different periods result in large variations in the levels of certain radionuclides, indicating that water levels can have a strong influence on radionuclide levels in reservoir regions. Hence, when evaluating the impact of large-scale water conservancy projects on radioactivity levels, analysis should be carried out on samples collected during different periods in order to make accurate assessments.